A phase I study of selinexor combined with weekly carfilzomib and dexamethasone in relapsed/refractory multiple myeloma. (15th February 2023) - Derman, Benjamin A; Chari, Ajai; Zonder, Jeffrey; Major, Ajay; Stefka, Andrew T; Jiang, Ken; Karrison, Theodore; Jasielec, Jagoda; Jakubowiak, Andrzej
Abstract: We performed a phase I study of weekly selinexor, carfilzomib, and dexamethasone (wSKd) in patients with relapsed/refractory multiple myeloma (MM). The primary objective was to identify the maximum tolerated dose (MTD) of wSKd. Secondary endpoints included overall response rate (ORR), progression‐free survival (PFS), and overall survival (OS). Prior exposure/refractoriness to carfilzomib was permitted. Thirty patients were enrolled; 26 (87%) had triple‐class exposed disease and 6 (20%) received chimeric antigen receptor (CAR) T‐cell therapy. Dose level 2 (carfilzomib 70 mg/m 2 Intravenous [IV] on Days 1, 8, and 15; selinexor 100 mg PO on Days 1, 8, 15, 22; dexamethasone 40 mg on Days 1, 8, 15, 22 of 28‐day cycles) was chosen as the MTD, with no DLTs having occurred. The most common hematologic adverse events (AE) were thrombocytopenia (83%), anemia (70%), lymphopenia (50%), and neutropenia (50%). The most common nonhematologic AE were fatigue (70%), nausea (70%), diarrhea (53%), and anorexia (47%). The ORR was 21/30 (70%) overall and 18/23 (78%) at the MTD. At a median follow‐up of 12.3 months, the median PFS was 5.3 months and median OS 23.3 months. Responses were similar in carfilzomib naïve and exposed patients. Long‐term efficacy of wSKd is modest; wSKd could be employed as a bridging strategy to immunotherapies.